Indoeuropeo, indo-hitita y nostrático - Alonso de la Fuente, José Andrés (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
In order to understand the deepest prehistory of the Indo-European languages is necessary to know the controversy about the «Indo-Hittite hypothesis». Of course, supporters of the «Nostratic hypothesis » must take into account this discussion too, above all because the «Indo-Hittite hypothesis» seems to corroborate many key aspects of the Nostratic reconstruction. The main goal of this paper is to show the degree of relationship between the classical version of the Proto-Indo-European language and these two proposals.